2007
DOI: 10.1128/aem.01931-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of Methanogenic Archaea in Adult Chicken Ceca

Abstract: By using molecular methods for the identification and quantification of methanogenic archaea in adult chicken ceca, 16S rRNA genes of 11 different phylotypes, 10 of which were 99% similar to Methanobrevibacter woesei, were found. Methanogen populations, as assessed by cultivation, and the 16S rRNA copy number were between 6.38 and 8.23 cells/g (wet weight) and 5.50 and 7.19 log 10 /g (wet weight), respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
4
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 28 publications
10
54
4
5
Order By: Relevance
“…This finding is consistent with other studies where Methanobrevibacter strains accounted for the vast majority of methanogens in chicken ceca (Saengkerdsub et al, 2007), the lower termite Reticulitermes speratus (Shinzato et al, 1999) and the rumen Sharp et al, 1998;Tokura et al, 1999;Whitford et al, 2001;Irbis and Ushida, 2004;Skillman et al, 2004Skillman et al, , 2006Wright et al, 2004Wright et al, , 2008. Moreover, this finding supports our hypothesis that the genus Methanobrevibacter is the most dominant constituent of foregut fermentation systems.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This finding is consistent with other studies where Methanobrevibacter strains accounted for the vast majority of methanogens in chicken ceca (Saengkerdsub et al, 2007), the lower termite Reticulitermes speratus (Shinzato et al, 1999) and the rumen Sharp et al, 1998;Tokura et al, 1999;Whitford et al, 2001;Irbis and Ushida, 2004;Skillman et al, 2004Skillman et al, , 2006Wright et al, 2004Wright et al, , 2008. Moreover, this finding supports our hypothesis that the genus Methanobrevibacter is the most dominant constituent of foregut fermentation systems.…”
Section: Discussionsupporting
confidence: 93%
“…The mean density of hoatzin crop methanogens (5.80 Â 10 9 cells per gram wet weight) from the present study was up to 20 000 times greater than methanogen densities found in chicken cecal samples, which were based on both most probable number enumeration and 16S rRNA copy numbers (Saengkerdsub et al, 2007). However, the mean density of methanogens in the hoatzin crop was in agreement with real-time PCR densities of methanogens from cattle from Canada using 16S rRNA (7.93 Â 10 4 to 1.62 Â 10 9 ; Hook et al, 2009), and cattle from Australia using the mcrA genes (9.8 Â 10 8 , Evans et al, 2009;1.34 Â 10 9 , Denman et al, 2007).…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Methanobrevibacter ruminantium was the highest represented methanogen (64.5%) in the crop of the hoatzin, followed by a substantial representation of unassigned Methanobrevibacter species (21.3%) and unassigned Methanosphaera species (13.2%; Wright et al, 2009). In chickens, Methanobrevibacter woesei was found to be the most prevalent methanogen in the ceaca (96.7%; Saengkerdsub et al, 2007). This was the first report of M. woesei as the most prevalent methanogen in a GIT.…”
Section: Birdsmentioning
confidence: 78%